ENVIRONMENTAL DECISION-MAKING THROUGH ADJUDICATORY APPEALS IN THE UNITED STATES - Tzoumis, Kelly; Shibilski, Emma (PEOPLE: International Journal of Social Sciences, 2019)
This research examines the appeals process of decisions made by the United States Environmental Protection Agency (EPA). As part of an adjudicatory appeals process, the Environmental Appeals Board (EAB) was established in 1992 internal to the EPA to review the decisions of the agency in specific areas. The purpose of the EAB was to serve as a neutral arbitrator that assists in the expeditious corrections of error which includes providing for consistency of policymaking and alleviation of cases proceeding to the federal court system. This research explores if the EAB has lived up to its charter. Research questions include what are the outcomes of these EAB adjudicatory appeal hearings? Are some environmental laws challenged more than others? More importantly, what is the impact of the federal courts on this EAB adjudicatory appeal process? For instance, are the courts in disagreement or generally affirm EAB decisions? And, overall, how long does this process take for a petitioner who files an EAB appeal and then moves the case into the federal courts for a remedy? Using publicly available data, decisions are analyzed from 1992-2018 (n=1014) by the EAB in regard to the type of appeal, the environmental legislation and programs involved as well as the duration of time for EAB decision-making over time. In addition, the outcome of the appeals to the federal courts (n=83) during this same time period are investigated to determine the efficaciousness of this process for an appellant. Results show that permits are 1.5 times more likely to be appealed versus other actions like penalties or consent orders before the EAB. Water issues (30.5%) are more likely to be appealed to the EAB than air (24.9%) or other cases. Based on data from January 2006 to January 2019 (n=552), the EAB has improved its processing time to provide decisions from approximately 7 months to 3 months. Only 8% of the EAB cases advance to the federal court system. However, the results indicate that appellants are not likely to have their case reversed by the federal court system. Only 13% of the EAB cases at the federal courts are reversed, and 9.6% are remanded back to the EAB, and 20.5% are affirmed. The majority of cases are either dismissed or denied (56.6%). This means that the original decision of the EAB remains intact for 77% of the cases heard at the federal courts. These results suggest some guidance to polluters early in the permitting process, particularly in water and air, could improve EPA decision-making preventing the need for cases coming before the EAB. The results indicate more guidance or clearer standards for implementation of permits is required by the EPA to polluters. In addition, the EAB appears to not be a major adjudicatory appeals venue for appellants, although the federal courts appear to be even less so which could mean the role of neutral arbitrator has not been achieved.